2002
DOI: 10.1385/mb:21:3:211
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan Decarboxylase from Transformed Roots of Catharanthus roseus

Abstract: Tryptophan decarboxylase (TDC, EC 4.1.1.28) from Catharanthus roseus hairy roots was purified 80-fold. Antibodies against TDC were obtained and they recognized only one protein of 55 kDa in crude extracts from hairy root cultures. Elicitation of transformed root cultures with macerozyme yielded a marked increase in TDC activity, which was accompanied by a similar increase in the amount of immunoreactive TDC protein. These results suggest that the alkaloid accumulation, produced by elicitation, requires the syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…This cytosolic localization correlates with the absence of targeting signal within the primary sequence of TDC, based on bioinformatic analysis, as was also hypothesized to hold true for the first 13 residues of the protein that are truncated in the C. roseus cell‐purified TDC [26,27]. In addition, both BiFC and yeast two‐hybrid assays established that TDC occurs as homo‐oligomers in vivo (Figs 5 and 6) in agreement with purification experiments [28–31]. On the basis of these experiments that allowed the purification of a 110 kDa protein, as well as the molecular weight of the TDC monomer (55 kDa), it could be hypothesized that TDC occurs at least as homo‐dimers in vivo .…”
Section: Discussionsupporting
confidence: 69%
“…This cytosolic localization correlates with the absence of targeting signal within the primary sequence of TDC, based on bioinformatic analysis, as was also hypothesized to hold true for the first 13 residues of the protein that are truncated in the C. roseus cell‐purified TDC [26,27]. In addition, both BiFC and yeast two‐hybrid assays established that TDC occurs as homo‐oligomers in vivo (Figs 5 and 6) in agreement with purification experiments [28–31]. On the basis of these experiments that allowed the purification of a 110 kDa protein, as well as the molecular weight of the TDC monomer (55 kDa), it could be hypothesized that TDC occurs at least as homo‐dimers in vivo .…”
Section: Discussionsupporting
confidence: 69%
“…crenulata for the first time. The sequence comparison analysis revealed that RcTYDC was similar with TYDCs of Opium poppy and Citrus species (about 50% identity) and TDCs of Catharanthus roseus (48.2% identity) [14] and Rauvolfia verticillata (46.3% identity) [15]. So, the only way to functionally identify TYDC was to feeding intermediate to recombinant TYDC.…”
Section: Discussionmentioning
confidence: 97%
“…The different sera used were G10H-preimmune serum, commercial preimmune serum (Zymed, cat. 01-6101) and a preimmune serum obtained by bleeding rabbits before immunization with pure TDC (Islas- Flores et al, 2002). None of these preimmune sera were able to inhibit the 10-hydroxy geraniol formation (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…The percentage of inhibition was calculated taking as 100% the activity measured without antiserum (10 pKat mg À1 ). The antisera probed in this experiment were: (') anti-G10H; (K) anti-CA4H, (m) anti-ARP1; (J) commercial pre-immune serum (Zymed, cat 01-6101) and (&) a preimmune serum (before immunization with pure tryptophan decarboxylase (Islas-Flores et al, 2002). able to interfere with the G10H catalysis. The antisera used were the monospecific anti-CA4H (Werck-Reichhart et al, 1993) raised against the CA4H (CYP73A1) from Helianthus tuberosus and anti-ARP1 (O' Keefe and Leto, 1989) that was generated against a P450 polypeptide (CYP71A1) from P. americana.…”
Section: Resultsmentioning
confidence: 99%